Bibliometric Analysis of Publications on the Digital Nomad with VOSviewer - Hakan Saraç (Sosyal Siyaset Konferansları Dergisi)
The aim of this study is to examine the bibliometric characteristics of studies on digital nomadism published in the Scopus database to guide those who want to conduct research on digital nomadism. Studies on digital nomadism published in the Scopus database were systematically analysed under the headings of authors, citations, sources, countries, institutions, and keywords. The data obtained were examined and mapped in terms of bibliometric indicators using VOSviewer. In addition, in the literature review, studies on digital nomadism were examined in terms of variables such as the findings and analyses used. Using the keyword “digital nomad” in the Scopus database, 1,080 results were obtained by selecting the “all fields” tab. According to the results of the analysis, while most publications on digital nomadism are published in the journal “Proceedings of the Acm on Human-Computer Interaction,” the most cited journal is “Sociology.” In terms of the number of citations, it was found that the study “Mobility and Proximity” dated (2002) was the most cited study. It was also concluded that the author who published the most publications was Daniel Schlagwein. The most cited institution was Unk “Syracuse University.” It was determined that the most publishing country was the USA and the most used keywords in terms of keywords were “digital nomads,” “Covid-19,” “remote working,” “digital nomadism” and “mobility.” This study found that interest in digital nomadism has increased rapidly in recent years, mainly because of the acceleration of the transition to remote working due to the Covid-19 pandemic, the increase in the opportunity to work remotely with technological developments, and the opportunity to work while travelling. On the other hand, although digital nomadism is generally associated with freedom and flexibility, difficulties in managing work-life balance, the difficulties of constant travel, and the lack of stability and regular income encourage researchers to conduct more studies in this field. In this context, the data obtained can guide future studies.